2022
DOI: 10.11591/ijece.v12i5.pp4820-4831
|View full text |Cite
|
Sign up to set email alerts
|

In-wheel, outer rotor, permanent magnet synchronous motor design with improved torque density for electric vehicle applications

Abstract: In electric vehicle applications, the torque density of electric motor plays an important role in improving the performance of the vehicle. The main objective of this paper is to investigate a possible method for improving the torque density of a permanent magnet synchronous motor used in electric vehicles. At the same time, other machine specifications were taken into account and kept within the acceptable level. This was achieved by incorporating performance enhancement strategies such as investigating ofhig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Additionally, examining the studies on outer-rotor PMSM from the literature reveals a predominant focus on surface-mounted structures [10][11][12][13]. When examining outer-rotor PMSM, it is observed that these motors effectively meet the demand for high torque at low speeds and are suitable for direct drive applications.…”
Section: Introduction (Gi̇ri̇ş)mentioning
confidence: 99%
“…Additionally, examining the studies on outer-rotor PMSM from the literature reveals a predominant focus on surface-mounted structures [10][11][12][13]. When examining outer-rotor PMSM, it is observed that these motors effectively meet the demand for high torque at low speeds and are suitable for direct drive applications.…”
Section: Introduction (Gi̇ri̇ş)mentioning
confidence: 99%
“…Mustafa Yaseen Bdewi et al employed an optimization method to enhance the magnet span, slot width, and slot opening of an outrunner PMSM. This approach was undertaken with the objective of improving torque density performance and maintaining low torque ripple over a wide range of current densities [12]. Also, Muhammed Muhsin Coşdu et al used a multiobjective differential evolutionary optimization algorithm (MODE) on an external rotor PMSM hub motor for the "Efficiency Challenge" competition to determine its lightweight potential [13].…”
Section: Introduction 1research Background and Motivationmentioning
confidence: 99%
“…Electrical Vehicles [1], Robotics [2], Power generation [3] and other industries use Surface-Mounted Permanent Magnets Synchronous Motors (SPMSMs). This is thanks to their high power density, high efficiency, ease to manufacture and compact structure.…”
Section: Introductionmentioning
confidence: 99%